2001
DOI: 10.1007/s004250000394
|View full text |Cite
|
Sign up to set email alerts
|

Cinnamic acid is a precursor of benzoic acids in cell cultures of Hypericum androsaemum L. but not in cell cultures of Centaurium erythraea RAFN

Abstract: Benzoic acids are precursors of xanthone biosynthesis which has been studied in cell cultures of Hypericum androsaemum (Hypericaceae) and Centaurium erythraea (Gentianaceae). In both cell cultures, methyl jasmonate induces the intracellular accumulation of a new xanthone. Under these inductive conditions, feeding experiments were performed with [U-14C]L-phenylalanine, [7-14C]benzoic acid and [7-14C]3-hydroxybenzoic acid. All three precursors were efficiently incorporated into the elicited xanthone in H. andros… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

9
60
0
1

Year Published

2003
2003
2017
2017

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 47 publications
(70 citation statements)
references
References 40 publications
9
60
0
1
Order By: Relevance
“…It has been reported that a 2% solution of NaB in drinking water is safe for lifelong treatment in mice without any noticeable side effects (12). In accordance with the published reports (13,14), a minor amount of benzoic acid, a direct metabolite of cinnamic acid (15), is also excreted in the urine of humans.…”
Section: Ultiple Sclerosis (Ms)supporting
confidence: 73%
See 1 more Smart Citation
“…It has been reported that a 2% solution of NaB in drinking water is safe for lifelong treatment in mice without any noticeable side effects (12). In accordance with the published reports (13,14), a minor amount of benzoic acid, a direct metabolite of cinnamic acid (15), is also excreted in the urine of humans.…”
Section: Ultiple Sclerosis (Ms)supporting
confidence: 73%
“…Semiquantitative RT-PCR was conducted as described earlier (19) using a RT-PCR kit from BD Clontech. In brief, 1 g of total RNA was reverse transcribed using oligo(dT) [12][13][14][15][16][17][18] as primer and Moloney murine leukemia virus reverse transcriptase (BD Clontech) in a 20-l reaction mixture. The resulting cDNA was appropriately diluted, and diluted cDNA was amplified using Titanium TaqDNA polymerase and following primers.…”
Section: Semiquantitative Rt-pcr Analysismentioning
confidence: 99%
“…Este estudio proporcionó asimismo la primera evidencia genética de una vía directa shiquimato/corismato para la síntesis de BA en las plantas. Estudios adicionales que apoyan esta hipótesis, pero que no proporcionan una evidencia directa de esta vía, incluyen: primero, la correlación de acumulación de DHBA con actividad ICS en cultivos celulares de Catharanthus roseus (Van Tegelen et al, 1999) y segundo, la incorporación de 3HBA radiomarcado en el radical benzoilo de xantonas junto con la falta de inducción de fenilalanina amonio liasa (PAL) en células de Centaurium erythraea (Abd El-Mawla et al, 2001).…”
Section: Ba Biosynthesis From Shikimate/chorismate Pathwayunclassified
“…Thus, 14 C-labelled phenylalanine (7) was reported to be incorporated into xanthones from Gentiana lutea, albeit with low incorporation rates [10], and label from cinnamic acid and benzoic acid was diverted to the xanthone, mangostin, in Garcinia mangostana [11,12]. Similarly, the benzoyl moiety of xanthone was claimed to be derived from L-phenylalanine in H. androsaemum via cinnamic acid, cinnamoyl-CoA, benzaldehyde, benzoic acid and hydroxybenzoic acid [13,14]. These reports supported earlier data on the origin of C 6 -C 1 units via the phenylpropanoid pathway [15][16][17].…”
mentioning
confidence: 99%
“…1) supplies building blocks for a wide variety of plant metabolites via phenylalanine (7), such as lignin, stilbenes and flavonoids, or via early pathway intermediates as specific precursors. Differentiation between these alternatives is possible by retrobiosynthetic analysis using general 13 C-labelled precursors (e.g. glucose; reviewed in [1]).…”
mentioning
confidence: 99%